Respuesta :

To solve this, plug in the expression equal to x for x in the first equation.

2x - 3y = 2
x = 6y - 5

2(6y - 5) - 3y = 2
Use the distributive property.
2 • 6y = 12y
2 • -5 = -10

12y - 10 - 3y = 2
Combine like terms.
12y - 3y = 9y

9y - 10 = 2
Add 10 to both sides.
9y - 10 + 10 = 9y
2 + 10 = 12

9y = 12
Divide both sides by 9.
9y / 9 = y
12 / 9 = 1.3333...
y = about 1.33

x = 6y - 5
y = 1.33
Plug in the value of y in the expression equal to the value of x.

x = 6(1.33) - 5
Solve.
6 • 1.33 = 7.98
x = 7.98 - 5
7.98 - 5 = 2.98

Final answer:
x = 2.98
y = 1.33
As an ordered pair, this is (2.98, 1.33).

Hope this helps!